A Rare Case of Ebstein’s Anomaly with Biventricular Noncompaction - Immaneni Sathyamurthy; Anuradha Sridhar; Sasikala Subramanian; Zeeshan Sakina A. Lakhani (Journal of Indian College of Cardiology)
Ebstein’s anomaly is a rare cyanotic congenital heart disease, which can present with right heart failure when associated with septal defects and/or right ventricular outflow tract obstruction. Left ventricular failure is extremely rare, and we report one such case due to the coexistence of biventricular noncompaction.